Can psychological characteristics, football experience, and player status predict state anxiety before important matches in Danish elite-level female football players? - Madsen, E. E.; Hansen, T.; Thomsen, S. D.; Panduro, J.; Ermidis, G.; Krustrup, P.; Wikman, J. (Scandinavian Journal of Medicine & Science in Sports, 2022)
Elite football can make players feel nervous, and personality characteristics, as well as experience, affect how well pressure is handled before important games. Studying the psychological characteristics of female football players can provide information on how well psychological pressure is handled and generate knowledge on how to support players in order to improve performance. Based on a sample of 128 female elite football players from 8 top-level teams, the present study investigates whether psychological characteristics and football experience/player stus in elite female football players can predict state anxiety before important matches. Our results outline that high age and national team experience negatively predicted most of the trait anxiety subscales. In line with previous research, no psychological differences were found between goalkeepers, defenders, midfielders, and strikers while starting players revealed to have significantly lower trait anxiety. When measuring before important matches, we found that somatic state anxiety was negatively associated with senior national team experience and positively associated with worry trait anxiety and fear of failure. Cognitive state anxiety was negatively associated with hope for success and positively associated with somatic and worry trait anxiety. Self-confidence was positively associated with youth national team experience and negatively associated with worry trait anxiety. It can be concluded that psychological characteristics and national team experience are both important for optimal state anxiety before important matches in elite-level women's football. Implications for practice and future research are discussed.